Asuhan Keperawatan Jiwa pada SDR. T Dengan Masalah Utama Isolasi Sosial : Menarik Diri Akibat Skizofrenia Tak Terinci di Ruang Gatotkaca RSJD Dr. Amino Gondohutomo Provinsi Jawa Tengah - Fandi Fannanul Khadiq; Slamet Wijaya; Esti Nur Janah (STIKES Columbia Asia Medan, 2024)
Health is a state of complete physical, mental and social well-being, not just freedom from disease or weakness (Maulina et al., 2024). According to WHO, (2022) Mental health is a state of mental well-being that allows a person to overcome the stresses of life, realize their abilities, contribute to their community, learn and work well. Someone who looks physically healthy does not mean they are mentally healthy. In general, mental health is a person's ability to process stress so that they function normally in carrying out their life to avoid symptoms of mental disorders. According to Sarmini, (2023) with a healthy mentality a person can carry out activities as a living creature, so it is said that mental health has an important role in a person's life.